Habitus of Harmony and Digital Adaptation: Interreligious Coexistence in Rural Indonesia during the Disruptive Era - Huda MF, Moh. Shofiyul; Tasmin, Tasmin; Al-Akiti, Muhammad Ayman (UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes the habituation practices of interreligious harmony in the disruptive era by examining Tanon Village, a multi-faith rural community in Kediri Regency, East Java, Indonesia. The village represents a unique case of long-standing plural coexistence that has successfully transitioned into the digital age. Employing a qualitative descriptive-analytical approach, the research integrates Pierre Bourdieu’s theoretical framework. Data were collected through in-depth interviews, field observations, and documentation of both offline and online interactions, including community WhatsApp groups and YouTube-based content. The findings reveal three interrelated dimensions that sustain harmony the reproduction of habitus through everyday interfaith practices such as slametan, gotong royong, and mutual participation in religious festivities; the adaptation of habitus within the digital field, where technology facilitates new forms of dialogue, coordination, and symbolic representation; and the integration of social and cultural capital through collaboration among religious leaders, youth, and village officials, reinforcing trust, empathy, and inclusivity. Together, these mechanisms demonstrate that interreligious harmony in Tanon is organic, adaptive, and transgenerational—rooted in local traditions yet responsive to technological change. The findings affirm that digital technology, when grounded in moral and cultural capital, can strengthen rather than threaten interfaith relations. The originality of this research lies in its integration of Bourdieu’s theoretical framework with digital ethnography, producing a new perspective for understanding how traditional values of tolerance are rearticulated and sustained within an ever-evolving digital ecosystem.